THE ACTUAL STATUS OF WORKING ENVIRONMENT AND THE MANAGEMENT OF WORKERS' HEALTH AT DONG ANH INVESTMENT BUILDING MATERIALS ROOFING JOINT STOCK COMPANY, HANOI IN 2021 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2022)
From January 2021 to June 2021, we conduct monitoring and evaluation of the working environmentand the management of occupational safety and health at the AC roof sheet production facility of“ Dong Anh Building Materials Roofing Joint Stock Company” we obtained the following results:The percentage of samples measured for microclimate factors did not meet the allowable standardswas 10.7%. The percentage of total dust samples exceeding the permissible standard is 2.1%, nosamples of asbestos fiber dust and respiratory dust exceeding the permissible standards. The contentof occupational safety and health management has been well implemented, accounting for 71.5 -100%. On site inspection, the percentage of units that strictly comply with regulations on occupationalsafety and health is not high, accounting for 25 - 43.8% depending on each specific indicator.
Keywords: Heath status, medical condition, working environment.